2006
DOI: 10.1097/01.prs.0000225439.39352.ce
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Wound Dressings on Cell Viability and Proliferation

Abstract: The principle of minimizing harm should be applied to the choice of wound dressing. Silver-based dressings are cytotoxic and should not be used in the absence of infection. Alginate dressings with high calcium content affect keratinocyte proliferation probably by triggering terminal differentiation of keratinocytes. Such dressings should be used with caution in cases in which keratinocyte proliferation is essential. All dressings should be tested in vitro before clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
114
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(124 citation statements)
references
References 21 publications
6
114
1
1
Order By: Relevance
“…Based on the MTT data one could expect approximately 100% cell death, which was supported by light microscope pictures. This is also supported by previous work showing that silver ions are toxic to skin cells in vitro (Barnea, Weiss & Gur, 2010;Burd et al, 2007; Paddle- Ledinek, Nasa & Cleland, 2006;Poon & Burd, 2004).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Based on the MTT data one could expect approximately 100% cell death, which was supported by light microscope pictures. This is also supported by previous work showing that silver ions are toxic to skin cells in vitro (Barnea, Weiss & Gur, 2010;Burd et al, 2007; Paddle- Ledinek, Nasa & Cleland, 2006;Poon & Burd, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…Our data are in consistence with the work done by Čolić et al (Čolić, Mihajlović, Mathew, Naseri & Kokol, 2015) showing reduced metabolic activity and cell proliferation, but low cytotoxicity for CNF. Also AquaCel ® has previously been shown to give a reduction in cell proliferation, but not affecting survival in keratinocytes (Paddle-Ledinek, Nasa & Cleland, 2006). CNF dispersion (50 µg/ml) did not affect the fibroblasts or the keratinocytes during the 24 h incubation, showing that a potential leakage of CNFs in a wound could be acceptable.…”
Section: Discussionmentioning
confidence: 97%
“…Owing to its antibacterial property, silver is used for the production of SiNPs containing medical products, such as wound dressings, devices, and catheters, to lower the incidence of bacterial infections. 13 However, Paddle-Ledinek et al 14 found that extracts from wound dressings containing SiNPs were more toxic to keratinocytes among those nanomaterials tested. SiNPs are well known to be toxic to various tissues, such as lung, liver, brain, vessels, and reproductive organs.…”
mentioning
confidence: 99%
“…An optimum microenvironment and absence of cytotoxic factors are essential for the phase of epithelization of the wound healing process. In-vitro studies show that Acticoat is toxic to both keratinocytes and fibroblasts, suppressing proliferation at the same time (Andrew et al, 2005;Burd et al, 2007;Paddle-Ledinek et al, 2006). The monitored patients' clinical results do not demonstrate such an in-vitro effect.…”
Section: Discussionmentioning
confidence: 99%